Building Information Modeling as Assest Management Tool. Issue 28 (2016) - Guillen, A.J.; Crespo, A.; Gómez, J.; González-Prida, V.; Kobbacy, K.; Shariff, S.
Abstract: BIM models are transforming the way buildings or, in more general terms, facilities or infrastructures are conceived, designed, constructed and managed. But current use of BIM concentrates on preplanning, design, construction and project delivery rather than maintenance and operation management. This despite the fact that it is estimated that operation and maintenance phase constitutes approximately 60% of the total lifecycle cost of a facility or building. Asset Management, which is a broad discipline including Facilities Management (FM), provide an advance approach getting more efficiency and efficacy in the lifecycle management of building and facilities. This paper introduces how the development of AM in this particular field is going to be supported by the application of BIM models as key tool that will allow asset management information system effective implementation.